Analysis of Character Types and Maslow’s Theory on Emily Bronte’s Wuthering Heights - Mochamad Maskhur; Lailatul Musyarofah; Eka Fadilah; Arif Dwi Cahyono (ITScience (Information Technology and Science), 2023)
The elements of Victorian literature found in the novel Wuthering Heights were the greatest effects loved by the characters in the novel Wuthering Heights. The purpose of this study was to describe a reflection of the character types and Maslow’s hierarchy of needs theory in Emily Bronte’s Wuthering Heights Novel. The author uses a qualitative method to clearly describe the results. The theory used in this study was Edgar V. Roberts' character analysis and Maslow's theory of need hierarchy. First, the author identifies the characters and then classifies all the data into the type of hierarchy of needs. The author analyze of the Heathcliff’s, Catherine’s, and Hindley’s on Emily Bronte's Wuthering Heights, how could Abraham Maslow's theory analyze the characters in Heathcliff’s, Catherine’s, and Hindley’s on Emily Bronte's Wuthering Heights. Based on the research, the author’s describe five hierarchy of need in Emily Bronte's Wuthering Heights. They were physiological needs, safety needs, love and attribution needs, respect needs, and self-fulfillment needs. The characters were Heathcliff, Catherine, and Hindley. Heathcliff was arrogant and humble in the lasting fame and popularity of the novel. Catherine's Earnshaw is bohemian, beautiful, spoiled and often arrogant. Hindley relinquished control of family and arrogant.